2017
DOI: 10.3389/fneur.2017.00186
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Functional Electrical Stimulation on the Upper Limb and Interscapular Muscles of Patients with Stroke for the Improvement of Reaching Movements: A Feasibility Study

Abstract: IntroductionReaching movements in stroke patients are characterized by decreased amplitudes at the shoulder and elbow joints and greater displacements of the trunk, compared to healthy subjects. The importance of an appropriate and specific contraction of the interscapular and upper limb (UL) muscles is crucial to achieving proper reaching movements. Functional electrical stimulation (FES) is used to activate the paretic muscles using short-duration electrical pulses.ObjectiveTo evaluate whether the applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 50 publications
(61 reference statements)
1
12
0
Order By: Relevance
“…This study offers clinical relevance as it aims to test a newly developed rehabilitation intervention for people with a very weak upper limb post stroke. As previous research has separately identified the effectiveness of music therapy Functional Electrical Stimulation (Cuesta-Gómez et al, 2017) on the functional activity of the paretic upper limb, we hypothesize that the two combined will be beneficial to post-stroke upper limb function. The auditory feedback of music-making with FES may further motivate stroke survivors with limited to no function to engage in repetitive, intensive and task-specific practice (Hubbard, Parsons, Neilson, & Carey, 2009) throughout their rehabilitation.…”
Section: Discussionmentioning
confidence: 95%
“…This study offers clinical relevance as it aims to test a newly developed rehabilitation intervention for people with a very weak upper limb post stroke. As previous research has separately identified the effectiveness of music therapy Functional Electrical Stimulation (Cuesta-Gómez et al, 2017) on the functional activity of the paretic upper limb, we hypothesize that the two combined will be beneficial to post-stroke upper limb function. The auditory feedback of music-making with FES may further motivate stroke survivors with limited to no function to engage in repetitive, intensive and task-specific practice (Hubbard, Parsons, Neilson, & Carey, 2009) throughout their rehabilitation.…”
Section: Discussionmentioning
confidence: 95%
“…Since shoulder and elbow training only improves motor impairment in the shoulder and elbow [ 62 ], and that training of the wrist and finger extensors only improves hand function [ 63 ], FES systems should have the capacity of stimulating postural control muscles involving other anatomic regions, linking the trunk and ipsilesional side to improve UL function. In fact, evidence shows that the benefits of FES are greatest when UL muscles are trained in a synergic pattern [ 62 , 63 , 64 , 65 ]. Hence, it is important for an FES system to: (1) accurately assist functional tasks in a synergic way; (2) encourage user effort; and (3) ensure muscle recruitment selectivity [ 66 ].…”
Section: Ul Post Stroke Rehabilitation Factors That Should Be Conside...mentioning
confidence: 99%
“…In addition to the peripheral strengthening effects of NMES described above, there is evidence that changes in cerebral cortex function with NMES can enhance motor control. 36,37 Cuesta-Gómez et al 38 found that stimulation of the interscapular musculature, deltoid, triceps, and wrist extensors with a reaching task resulted in improved performance of the task, by increasing active shoulder flexion and elbow extension range of motion compared to use of placebo stimulation. This study did not include any measure of cerebral cortex function; however, other researchers found that cerebral cortex efficiency improved during motor tasks following a short application of NMES with volitional activity in the upper extremity.…”
Section: Background and Protocol For Neuromuscular Electrical Stimulamentioning
confidence: 99%